Human Trafficking : A Brief Overview - Makisaka, Megumi (World Bank, Washington, DC, 2012)
Millions of men, women and children are victims of human trafficking for sexual, forced labor and other forms of exploitation worldwide. The human and economic costs of this take an immense toll on individuals and communities. By conservative estimates, the cost of trafficking in terms of underpayment of wages and recruiting fees is over $20 billion. The costs to human capital are probably impossible to quantify. The problem of trafficking cuts across a range of development issues, from poverty to social inclusion, to justice and rule of law issues, and thus has relevance for practitioners throughout the development community. This note provides a brief overview on the issues of human trafficking, which can be used as a quick reference for the task team leaders, sector managers, directors, and their clients at the World Bank Group. This note will first provide a definition of human trafficking and the scope of the problem, and then summarize the regional trends of trafficking patterns. This is followed by a discussion of the key actors in the anti-trafficking movement and the role played by development partners in preventing human trafficking. The final section offers some potential orientations for the World Bank Group to further engage this issue in its operations.